PSYCHOLOGICAL CHARACTERISTICS OF THE DEVELOPMENT OF PROTECTIVE MECHANISMS AGAINST STRESS IN ADOLESCENTS IN EXTREME SITUATIONS (World Bulletin of Social Sciences, 2025)
Adolescents often face stress due to psychological immaturity, unstable emotional regulation, and limited coping resources. Extreme situations such as natural disasters, conflicts, social pressures, and traumatic events can trigger acute stress responses in this age group. This article explores the psychological features of adolescents’ stress protection mechanisms, emphasizing their developmental characteristics, social support systems, and adaptive strategies. The study analyzes literature on adolescent stress resilience, applies psychological assessment methods, and discusses results highlighting both protective and risk factors. Based on the findings, recommendations are made for strengthening stress-protection mechanisms through educational, clinical, and social interventions